Techniques used and efficacy of volleyball skills in relation to gender - Palao, J. M.; Manzanares, P.; Ortega, E. (International Journal of Performance Analysis in Sport, 2009)
The purposes of this study were to determine reference values for the techniques used and assess the efficacy of these techniques in relation to gender in volleyball. Twenty-two matches from the XVth Mediterranean Games of Almeria 2005 (38 sets for males and 39 sets for females) were analyzed. A descriptive, correlational, and transversal design was done. The variables analyzed were gender, type of technique, and efficacy of technique. The serve most used by males was the power jump serve and by females it was the standing serve. The serve was more effective for females than for males, while serve reception was more effective for males. The overhand set was the most used set for both males and females. When the set was done after a dig, the forearm contact was also used. Males had more effective sets than females. The standard attack technique was the most used attack. Attack efficacy was similar for both genders. The dig technique most often used was the forearm contact. Dig efficacy was similar for both genders. The data found show that use of the techniques and their efficacy are different for males and females; therefore, training methods should also be different.